(untitled) (Baghdad Science Journal, 2022)
Melanoidins can be diagnosed using the Fourier transform infrared (FTIR) technique. UV/Vis is an effective tool for both qualitative and quantitative analysis of chemical components in melanoidin polymers. The structural and vibrational features of melanoidin synthesized from D-glucose and D-fructose are identical, according to FTIR spectra, with the only difference being the intensity of bands. Using FTIR spectra, the skeleton of melanoidin is divided into seven major regions. The existence of the C=C, C=N, and C=O groups in all melanoidins formed from fructose and glucose with ammonia is confirmed by the areas ranging from 1600 to 1690 cm-1, and the band is largely evident as a broad shoulder. Both melanoidins have a carboxyl or carbonyl extending around 1700 cm-1. In all melanoidins, the NH+ group has vanished in the 3080 cm-1 range. However, the color intensity depends on the type of sugar employed in melanoidin synthesis. Furthermore, in comparison to Glc-ammonia, which has a higher proportion of sp3 hybridized carbon, Fru-ammonia has a higher proportion of sp2 hybridized carbon based on UV/Vis, FTIR and second-derivative spectra. Moreover, the data were simulated using principal component analysis. Principal component analysis (PCA) was used to interpret the data.